PENGARUH RASIO PROFITABILITAS (ROA), RASIO LIKUDITAS (CR) DAN RASIO AKTIVITAS (TATO), TERHADAP STRUKTUR MODAL (DER) PADA PERUSAHAAN BASIC INDUSTRY AND CHEMICALS DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Afni Laura Situmeang; Sapri Siagian; Nurbertiny Sigalingging; Yulia Giovani Samosir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2022)
This research aimed at testing and analyzing the effect of Return on Assets (ROA), Current Ratio (CR), Total Assets Turn Over (TATO) on Capital Structure in basic industry and chemicals companies which were listed in Indonesia Stock Exchange in 2014-2018 period. The research methodology used in this research was quantitative method with descriptive approach. The nature of this research was explanatory research. The population of this research was sixty six (66) basic industry and chemicals companies. By using sampling technique of purpose sampling, sixteen (16) basic industry and chemicals companies which met the criteria were taken as samples. The method of analyzing data applied in this research was double linear regression analysis with classic assumption test. The results showed that Return on Assets (ROA), Current Ratio (CR), Total Assets Turn Over (TATO) simultaneously and significantly had effect on Capital Structure in basic industry and chemicals companies which were listed in Indonesia Stock Exchange in 2014-2018 period with the result of Fcount ≥ Ftable or significance of 19,146 ≥ 2,72 and 0.000 ≤ 0,05. Partially, Return on Assets (ROA) had negative and insignificant effect on Capital Structure. Current Ratio (CR) had negative and insignificant effect on Capital Structure. Meanwhile Total Assets Turn Over (TATO) had no effect and had insignificant effect on Capital Structure. The results of the analysis of the coefficient of determination obtained adjusted R2 value which showed the variation of Capital Structure variable which could be explained by the variation of Return on Assets (ROA), Current Ratio (CR), Total Assets Turn Over (TATO) variables as much as 0.377 or equivalent with 37.7% meanwhile the rest as much as 62.3% was explained by the variation of other variations.